Modifying Tiny Service Discovery Protocol (MTinySDP) to overcome mobility issues - Kahloot, Khalid M.; ElKhatib, Akram A.; Salim, Ahmed A. (Arab Journal for Sciences and Research Publishing, 2016)
Emerging wireless communication standards and more capable sensors and actuators are pushing the development towards wireless sensor networks (WSNs). Deploying a large number of sensor nodes requires a high level framework enabling the devices to present themselves and the resources they hold. The device and the resources can be described as services. With a service discovery protocol, resources, e.g. samples of data produced by the sensor, could be provided to the application developers through high level interfaces. Service discovery protocols enable software, i.e. services and service users, to dynamically advertise and find available services on the network.The Tiny Service Discovery Protocol (TinySDP), as its name suggests, is a lightweight protocol that allows discovery and selection of services in WSN. Here, we have analyzed the TinySDP protocol with mobile WSN since adding mobility to sensor networks can significantly increase the capability of the sensor network by making it resilient to failures, reactive to events, and able to support disparate missions with a common set of sensors.In this paper, we perform analytical simulations in terms of Success ratio, number of transmitting messages and average waiting time. Simulation results show that the performance of TinySDP in mobile WSNs (MWSNs) has been decreased. As a result, we present Modified TinySDP (MTinySDP) for MWSNs. The simulation results show that MTinySDP outperforms TinySDP   in terms of Success ratio, number of transmitting messages and Average waiting time for mobile and static WSN.
Keywords: (Wireless Sensor Network (WSN; (Service Discovery Protocol (SDP; SDPMobility; MobilityTinySDP; TOSSIM; TinyViz